2021
DOI: 10.1017/s1368980021002974
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Mass Index, Emotional Eating and Perceived Stress during COVID-19 Partial Quarantine in Healthy Adults

Abstract: Objective: We investigated emotional eating behaviours and perceived stress during COVID-19 partial quarantine according to BMI levels in healthy adults. Design: Cross-sectional study. Setting: An online survey included demographic variables, eating attitude-related questions, Emotional Eater Questionnaire (EEQ), and Perceived Stress Score-14 (PSS-14) was sent via online data collection platform. Self-reported weight, height and weight changes during the quarantine were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
(106 reference statements)
2
30
0
1
Order By: Relevance
“…There were initially 1,496 answers, but 162 answers were excluded, resulting in 1,334 individuals enrolled in this study. Participants were 31 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years old the majority were women (79.8%) from the Southeast region of Brazil (89.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were initially 1,496 answers, but 162 answers were excluded, resulting in 1,334 individuals enrolled in this study. Participants were 31 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years old the majority were women (79.8%) from the Southeast region of Brazil (89.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The state of being depressed or the worsening of this condition are precursors for weight gain and recovery ( 26 ). On the other hand, Barcin-Güzeldere and Devrim-Lanpir ( 27 ) suggested that the stress transmitted by the COVID-19 pandemic can cause a reduction in appetite since some will want to increase the consumption of certain foods as a way to ward off emotions. Others do the opposite, that is, reducing their consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the lockdown related to the COVID-19 pandemic caused lots of emotional problems including anxiety, depression, and sleep disturbances. Many people began to cope with their emotions by increasing food (emotional eating) and alcohol consumption and in combination with decreased physical activity, promoted the development of overweight and obesity [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results so far indicate that for many people, COVID-19 was (or still is) a strong source of stress [ 4 , 22 , 24 ], and its high levels can lead to unhealthy eating behaviors [ 16 , 17 , 25 , 26 ]. These changes in eating were (and may still be) related to the fact that people use food as a way of regulating emotions, especially in a situation where other ways of coping with anxiety, stress, and other negative emotional states have been significantly limited by restrictions related to COVID-19 (including direct contact with friends, going to the cinema and other entertainment venues, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…These changes in eating were (and may still be) related to the fact that people use food as a way of regulating emotions, especially in a situation where other ways of coping with anxiety, stress, and other negative emotional states have been significantly limited by restrictions related to COVID-19 (including direct contact with friends, going to the cinema and other entertainment venues, etc.) [ 15 , 16 , 24 , 25 , 27 , 28 ]. In addition, the source of negative emotions may also be COVID-related restrictions, which, at some stage of the pandemic, prevented us from practicing physical activity outdoors, in the gym, and in other places of recreation [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%